The THE EFFECT OF LEVERAGE, FIRM SIZE, EARNING GROWTH, AND EARNING PERSISTENCE ON EARNING RESPONSE COEFFICIENT - Ferry Irawan; Lili Talpia (Center for Economic Studies Universitas Katolik Parahyangan, 2021)
This study aims to investigate the effect of leverage, firm size, earnings growth, and earning persistence on earnings response coefficient. The population used in this study are all manufacturing companies listed in Indonesia Stock Exchange from 2015 until 2019 and had positive earnings before tax. Consequently, the samples in this research are 68 manufacturing companies so that the observations are 340. For examining data, this research uses a panel data regression model. After running the chow test and Lagrange multiplier test, the most suitable method for the regression model is the common effect model. This research shows that leverage and firm size do not influence earning response coefficient. Meanwhile, earnings growth and earnings persistence have a positive effect on the earnings response coefficient. Keywords: Earning growth; earning persistence; earning response coefficient; firm size; leverage